2012
DOI: 10.14295/bds.2012.v15i1.737
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sterilization methods on the absorption capacity of absorbent paper points

Abstract: A BSTR A CTdifferent brands of standardized absorbent paper points, testing the hypothesis that there is a positive correlation between the percentage of increased absorption capacity and sterilization method. Standardized endodontic absorbent paper points (size rank from #15 to #40) from three different brands of three manufacturers were used for this study (Dentsply, Endopoints, Tanari). Twenty absorbent paper points of each size were used. The initial weight (iw) of each absorbent paper point was recorded u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
1
1
0
Order By: Relevance
“…Because autoclave sterilization is the most widely used method in dentistry owing to its speed and efficiency, it was decided that this investigation would determine whether this method affects the points of one of the brands most commonly used by students. This study found that there is no change in this characteristic, which has been reported by other studies [6,18,19].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Because autoclave sterilization is the most widely used method in dentistry owing to its speed and efficiency, it was decided that this investigation would determine whether this method affects the points of one of the brands most commonly used by students. This study found that there is no change in this characteristic, which has been reported by other studies [6,18,19].…”
Section: Discussionsupporting
confidence: 85%
“…The absorbent points are usually made up of cellulose with an added binder which imparts rigidity and prevents it from coming apart during use. Points are sold in assorted packaging of various sizes, diameter, and quantity, and must have the specifications of the International Organization for Standardization (ISO) [6]. Their characteristics include the capacity to absorb any type of fluid; having a uniform length; having a straight point shape; being white and odorless; having sufficient integrity under dry or wet conditions to prevent the release of fibers; and being free of microorganisms [6].…”
Section: Introductionmentioning
confidence: 99%